Robert Ludlum's the Bourne sacrifice [large type] - Freeman, Brian, 1963-; Ludlum, Robert, 1927-2001 (Ludlum, Robert, 1927-2001. Jason Bourne series, 2022)
"Jason Bourne has faced many killers before, but none as dangerous or as cruelly inventive as the assassin who calls himself Lennon. Bourne believes the assassin has a new employer called the Pyramid. The only clue to the group's agenda is a young German woman murdered in Washington on her way to a covert meeting. But the woman's entire identity turns out to be a lie, and news reports of her death have been strangely twisted and suppressed. Bourne will need to use every bit of his tradecraft and his genius for mayhem to expose this web of lies and murder"--